Case Report: Significant Efficacy of Pyrotinib in the Treatment of Extensive Human Epidermal Growth Factor Receptor 2-Positive Breast Cancer Cutaneous Metastases: A Report of Five Cases - Wang, Nan; Li, Lin; Xiong, Youyi; Chi, Jiangrui; Liu, Xinwei; Zhong, Chaochao; Wang, Fang; Gu, Yuanting (Frontiers in Oncology, 2021)
Background: Breast cancer (BC) is the most common tumor to develop cutaneous metastases (CM). Most BCs with cutaneous metastasis are human epidermal growth factor receptor 2 (HER2) positive subtypes. Although the molecular mechanisms of breast cancer metastasis to different sites and the corresponding treatment methods are areas of in-depth research, there are few studies on cutaneous metastasis. Case Presentation: Five HER2-positive BC patients with extensive cutaneous metastases were treated with a regimen containing pyrotinib, a novel small-molecule tyrosine kinase inhibitor that irreversibly blocks epidermal growth factor receptor (EGFR), HER2, and human epidermal growth factor receptor 4(HER4), then their cutaneous metastases quickly resolved at an astonishing speed and their condition was well controlled during the follow-up period. Conclusions: This case series reports the significant therapeutic effect of pyrotinib on cutaneous metastases of HER2-positive BC for the first time. Based on this, we recommend that pyrotinib can be used as a supplement to trastuzumab for HER2-positive BC patients with cutaneous metastases. In addition, we should consider that the pan-inhibitory effect of pyrotinib on EGFR, HER2 and HER4 may provide a dual therapeutic effect against HER2 and mucin 1(MUC1).